Trade and women - Ben Shepherd; Susan F. Stone (Asian Development Bank Institute (ADBI), 2017)
This paper studies the impact of migrant children on their parents' occupation choice and wage income using a dataset from a household survey conducted in 2011. We find that the heads of migrant households with school-age children earn significantly less than those who left them at their place of hukou registration. This result holds when we control for personal characteristics, migration duration, origin location, and family structure. Households migrating with school-age children have a higher probability of doing so within the prefecture/province of their hukou registration and are less likely to target coastal regions. After controlling for migration scope and destination location, the presence of children does not influence wages of migrant household heads. We also find that the presence of children below the age of six has no impact on the income of migrant household heads. Our results suggest that the hukou system still impedes labor mobility.
Keywords: J12; J13; J18; I28; 330; Economics; Gender; Industry and trade